2013
DOI: 10.1097/mao.0b013e318297638a
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Trial of Hyperbaric Oxygen Therapy and Intratympanic Steroid Injection as Salvage Treatment of Sudden Sensorineural Hearing Loss

Abstract: HBO and IT steroid therapy could be successfully used as salvage therapies in patients with sudden deafness. Further study is needed to demonstrate superiority of one of the treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
2
35
1
1
Order By: Relevance
“…While previous studies showed that younger patients had better response after HBO therapy, in our study, we found no hearing improvement related to age. Our study showed that HBO therapy as salvage therapy significantly improves the outcome in patients with a hearing loss of >61 dB, while some previous studies have found the benefit of HBO therapy only among patients presenting with profound hearing loss (>80 or >90 dB) [19,21,22] . In the group of patients with a hearing loss of ≤60 dB, improvement was noticed only at low frequencies (0.25 and 0.5 kHz), which is consistent with a previous study on SSNHL that showed that the apical part of the cochlea recover better than the basal parts [24] .…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…While previous studies showed that younger patients had better response after HBO therapy, in our study, we found no hearing improvement related to age. Our study showed that HBO therapy as salvage therapy significantly improves the outcome in patients with a hearing loss of >61 dB, while some previous studies have found the benefit of HBO therapy only among patients presenting with profound hearing loss (>80 or >90 dB) [19,21,22] . In the group of patients with a hearing loss of ≤60 dB, improvement was noticed only at low frequencies (0.25 and 0.5 kHz), which is consistent with a previous study on SSNHL that showed that the apical part of the cochlea recover better than the basal parts [24] .…”
Section: Discussioncontrasting
confidence: 41%
“…A comparison of these two methods was recently described [22,23] . Both methods have been successful.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Prior reports have revealed the advantage of HBO treatment just among the cases with profound hearing loss (>60, >80 or >90). [5,13] Similarly, we found that only patients with severe hearing loss (cut-off level of initial PTA was at 70 dB) had significant hearing improvement after HBO therapy. Previous studies on salvage HBO therapy reported mostly mean gains of hearing.…”
Section: Discussionmentioning
confidence: 66%
“…[12] Although prospective clinical trials of salvage HBO therapy with a control group are limited, result of these studies showed some benefits in hearing improvement. [10,13,14] The results of salvage HBO therapy in previous studies are demonstrated in Table 4. [9,[14][15][16][17][18] To date, no reports have been published about the hearing outcomes of salvage HBO therapy after combined steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas these treatments have been shown to improve hearing thresholds in patients with idiopathic sudden sensorineural hearing loss. 17,18 Intra tympanic steroid therapy has been shown to improve the hearing threshold in patients with sudden idiopathic sensorineural hearing loss. This procedure was undertaken after the patient failed to respond to systemic steroid therapy.…”
Section: 13mentioning
confidence: 99%